2018
DOI: 10.1186/s12864-018-5002-5
|View full text |Cite
|
Sign up to set email alerts
|

Whole-genome bisulfite sequencing of goat skins identifies signatures associated with hair cycling

Abstract: BackgroundHair follicles (HFs), upon development, undergo repetitive cycles of growth (anagen), regression (catagen), and rest (telogen). The transition between the stages is determined by multiple molecular signals, including DNA methylation, which plays important roles in mammalian cellular identity and is essential for the development of HFs. Secondary hair follicles (SHFs) in cashmere goat exhibit classic cyclic hair development, and little has been done on a genome-wide scale to examine potentially methyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 44 publications
4
27
0
Order By: Relevance
“…While previous studies have determined the effects of selected aspects, such as the genome-wide locus, DNA methylation, transcriptional signatures, and morphology, on the morphogenesis of curly fibers (Hynd et al, 2009;Cheng et al, 2010;Sriwiriyanont et al, 2011;Espada et al, 2014;Fan et al, 2015;Sennett et al, 2015;Gao et al, 2016;Glover et al, 2017;Li et al, 2018;Petridis et al, 2018), a comprehensive study conducting the interplay of genome-wide DNA methylation and transcription synchronously using skin tissues from the same biological replicates in different growth stages had thus far been lacking. The functional regulation of DNA methylation on gene expression has now been established as an effective prospective way to understand the ways that drastic methylation changes relate to hair phenotypic variation (Guo et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While previous studies have determined the effects of selected aspects, such as the genome-wide locus, DNA methylation, transcriptional signatures, and morphology, on the morphogenesis of curly fibers (Hynd et al, 2009;Cheng et al, 2010;Sriwiriyanont et al, 2011;Espada et al, 2014;Fan et al, 2015;Sennett et al, 2015;Gao et al, 2016;Glover et al, 2017;Li et al, 2018;Petridis et al, 2018), a comprehensive study conducting the interplay of genome-wide DNA methylation and transcription synchronously using skin tissues from the same biological replicates in different growth stages had thus far been lacking. The functional regulation of DNA methylation on gene expression has now been established as an effective prospective way to understand the ways that drastic methylation changes relate to hair phenotypic variation (Guo et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Some critical signaling pathways, including the wingless-related integration site (WNT), ectodysplasin A receptor (EDAR), and bone morphogenetic proteins (BMP) pathways, are regarded as regulatory hubs during fiber development (Lu et al, 2016;Telerman et al, 2017). Mammals, and in particular, sheep and goats have obvious periodic fiber growth with seasonal changes, and the regulatory mechanisms of these changes have been explored in transcriptome studies (Yang et al, 2017;Li et al, 2018). Subsequently, some genetic factors, such as those of the TCHH, KRT gene families, and the metallothionein 3 isoforms, which are related to curly wool, h a v e b e e n d e t e r m i n e d b y R N A -s e q a n a l y s i s a n d immunohistochemical analyses of the fiber proteins (Sriwiriyanont et al, 2011;Yu et al, 2011;Kang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Y. revealed 10 DMRrelated genes (DMGs) by analyzing the sequencing results of Hu sheep ovaries, which were likely related to the prolificacy of Hu sheep. Li et al (2018) identified potential DMRs and DMGs that were involved in hair follicle development and growth in cashmere goats. Dechow and Liu (2018) detected the DNA methylation patterns in peripheral blood mononuclear cells of Holstein cattle with variable milk yield, and revealed some potential epigenetic variation related to milk performance.…”
Section: Discussionmentioning
confidence: 99%
“…Cashmere is an important economic product worldwide and the world market for cashmere is increasing, but the current production of cashmere is limited [1][2][3][4]. Albas cashmere goat, famous across the world for its high-quality cashmere, is one of the most precious genetic resources on the Inner Mongolia Plateau in China [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Due to their important role in cashmere growth, SHF-DPCs serve as an excellent model to investigate the function mechanism of genes on HF in cashmere goats [19][20][21][22]. Therefore, to improve the individual cashmere production of cashmere goats, researchers tried to find the major genes and pathways that may affect the growth and development of SHF-DPCs and HF cycle by transcriptomics and bioinformatics methods [4,12,23].…”
Section: Introductionmentioning
confidence: 99%